Perancangan Sistem Booking Lapangan Badminton Berbasis Web Menggunakan Algoritma First In First Out - Muhammad Imron Yusup; Tri Dharma Putra; Andy Achmad Hendharsetiawan (Journal of Informatic and Information Security, 2023)
Badminton is a sport that is in great demand by people, from children to adults. GOR WGN Sport Center is one of the businesses engaged in badminton sports field rental services located in Bekasi City. In terms of field rental services, they still use the manual method by visiting the location directly, which is less effective. With this lack of information, customers do not know the field rental schedule in real time, so information related to the schedule is urgently needed. For this reason, in leasing the field at the WGN Sport Center Sport Center, an information system related to website-based field rental is needed which will make it easier for customers to find information in the field booking process and field rental schedules in real time. The algorithm used is the First In First Out (FIFO) algorithm. In the FIFO algorithm data buffering is regulated and manipulated based on the fact that the first incoming data will be processed first, that is, in its implementation, the first customer to make a field booking will be served first.